The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Patty's Toxicology 2000
DOI: 10.1002/0471435139.tox052
|View full text |Cite
|
Sign up to set email alerts
|

Polycyclic and Heterocyclic Aromatic Hydrocarbons

Abstract: Aromatic hydrocarbons are the class of chemicals that include multi‐ring aromatic compounds. Smaller aromatic hydrocarbons, one to two rings, are of considerable economic importance as industrial raw materials, solvents, and components of innumerable commercial and consumer products. However, aromatics differ vastly in chemical, physical, and biological characteristics from the aliphatic and alicyclic hydrocarbons. In addition, aromatics are more toxic to humans and other mammals. Of prime importance are the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 136 publications
0
0
0
Order By: Relevance
“…Benzo[a]pyrene is the most common PAH with established mutagenicity (Stiborova et al, 2016) while phenazine is a NPAH recently identified as a disinfectant-by-product (DBP) in drinking water (Zhao et al, 2008) and there is no information; its mutagenic activity is limited. Similarly, 2methylnaphthalene has been detected in appreciable quantity in emissions from cigarettes, coal tar pitch, petroleum refineries, emission engines, and diesel exhaust fumes (HSDB, 2002;Warshawsky, 2001;ASTDR, 2005). 2-methylnaphthalene is absorbed rapidly post-ingestion, distributed and metabolised among tissues lungs and liver in less than 6 h (Melanon et al, 1982;Teshima et al, 1983;Ding et al, 2005;Fang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Benzo[a]pyrene is the most common PAH with established mutagenicity (Stiborova et al, 2016) while phenazine is a NPAH recently identified as a disinfectant-by-product (DBP) in drinking water (Zhao et al, 2008) and there is no information; its mutagenic activity is limited. Similarly, 2methylnaphthalene has been detected in appreciable quantity in emissions from cigarettes, coal tar pitch, petroleum refineries, emission engines, and diesel exhaust fumes (HSDB, 2002;Warshawsky, 2001;ASTDR, 2005). 2-methylnaphthalene is absorbed rapidly post-ingestion, distributed and metabolised among tissues lungs and liver in less than 6 h (Melanon et al, 1982;Teshima et al, 1983;Ding et al, 2005;Fang et al, 2006).…”
Section: Introductionmentioning
confidence: 99%